Uroflowmetry: nomograms in healthy young Pakistani men - Sheikh, Masood Ahmed; Ali, Shahzad; Khan, Ayesha (Journal of the Pakistan Medical Association, 2024)
Objective: To create a nomogram based on urine volume and flow of males without lower urinary tract symptoms. Method: The prospective, cross-sectional study was conducted at the Department of Urological Surgery and Transplantation, Jinnah Postgraduate Medical Centre, Karachi, from November 1, 2020, to October 31, 2022, and comprised healthy young males without lower urinary tract dysfunction who were recruited from the hospital as well as a large textile mill. They were asked to void on their normal desire. Uroflowmetry was done to determine maximum flow rate, average flow rate, and void volume values. A best-fit regression model was used to formulate uroflowmetry nomogram using average and maximum urine flow rate over voided volume. The sample size was calculated using PASS 2020 Power Analysis and Sample Size Software (2020). NCSS, LLC. Kaysville, Utah, USA. The database was developed on NCSS 2020 Statistical Software (2020). NCSS, LLC. Kaysville, Utah, USA for the data analysis. Results: Of the 468 male subjects enrolled, data was analysed related to 432(92.3%). The mean age was 25.59±4.32 years. Mean maximum flow rate, average flow rate and void volume were 25.28±8.70mL/s, 14.77±4.79mL/s and 405.48±163.86mL, respectively. The association of age was noted with maximum flow rate (r=0.1435, p=0.004), average flow rate (r=0.1135, p=0.004) and void volume (r=0.0619, p=0.004). The best-fitted model for maximum and average flow rate was subsequently developed which was statistically significant (p<0.05). Conclusion: The nomograms developed could reliably predict the maximal flow rate in young Pakistani men. Key Words: Nomogram, Maximum flow rate, Lower urinary tract symptoms, Pakistan.